Manajemen Organisasi Olahraga dalam Pengembangan Prestasi Atlet Daerah: Studi Kasus Askab PSSI Kabupaten Malaka - Klau, Maksimus; Talan, Rudobertus; Liunokas, Oded; Ajito, Timoteus (Indo-MathEdu Intellectuals Journal, 2026)
Sports organization management plays a strategic role in developing the achievements of regional athletes, particularly in soccer, which requires a sustainable training system. This study aims to analyze the organizational management of the Askab PSSI (Soccer Association of Indonesian Football Associations) in Malaka Regency in developing the achievements of regional athletes. The study used a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation with Askab PSSI administrators, coaches, and PS Malaka athletes. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results indicate that Askab PSSI management in Malaka Regency has implemented planning, organizing, implementing, and supervising functions in athlete development, but still faces obstacles in funding, infrastructure, and program continuity. These findings confirm that structured and sustainable sports organization management contributes to improving the achievements of regional athletes. This research provides practical implications for regional sports organization managers in optimizing athlete management training systems